Morphological Characteristics of Gamma-Irradiated Desmanthus virgatus Mutants Adapted to High Salinity Conditions - Ramadani, Jidan; Prihantoro, Iwan; Dewi MHKS, Panca (Buletin Peternakan, 2024)
Gamma-ray irradiation can induce plant mutations, resulting in stable genetic changes that persist in future generations. This study aims to assess the morphological characteristics of the potential mutant of Hedge Lucerne (Desmanthus virgatus) that has developed adaptation to high salinity conditions as a result of irradiation using gamma-ray. A total of 36 candidate mutants first generation (M1) of D. virgatus were used in this study, and they had developed adaptation to high salinity conditions (8.4 dS/m) and were observed 64 wk after planting. The collected data underwent a descriptive statistical analysis and succeeded by applying the Shapiro-Wilk test to assess the normality of the data distribution. A concentration index greater than one (>1.00) signifies a high value of the plant’s morphological characteristic. All levels of gamma irradiation groups produced an excellent survival response in the mutant candidate. The high diversity in morphological characteristics was reflected in the number of compound leaves, the width of compound leaves, and the number of leaves per pinnae, flowers, and pods. The dominant color of the lower leaves was 7.5 Green Yellow (5/6), and the middle leaves were 7.5 Green Yellow (5/6), while the dominant color of the upper leaves was 7.5 Green Yellow (6/8). The mutant candidate of D. virgatus exhibited the best characteristics, as determined by the concentration index, were those subjected to 200 Gray and 300 Gray irradiation. Fifteen superior mutant candidates were identified, namely GDV100.1, GDV100.2, GDV100.4, GDV100.5, GDV200.2, GDV200.3, GDV200.7, GDV200.9, GDV200.10, GDV300.3, GDV300.4, GDV300.5, GDV300.12, GDV300.13. and GDV 500.1. The three best mutant candidates (M1) were GDV100.2, GDV200.3, and GDV500.1. The three best mutant candidates (M1) were GDV100.2, GDV200.3, and GDV500.1.